2015
DOI: 10.1007/s10209-015-0440-1
|View full text |Cite
|
Sign up to set email alerts
|

User interface design guidelines for smartphone applications for people with Parkinson’s disease

Abstract: Parkinson's disease (PD) is often responsible for difficulties in interacting with smartphones; however, research has not yet addressed these issues and how these challenge people with Parkinson's (PwP). This paper specifically investigates the symptoms and characteristics of PD that may influence the interaction with smartphones to then contribute in this direction. The research was based on a literature review of PD symptoms, eight semi-structured interviews with healthcare professionals and observations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
(67 reference statements)
3
29
0
Order By: Relevance
“…This work contributes a deeper understanding of ME/CFS patients' needs for self-management technologies. The studies also affirm the results of prior work [11,56], which has highlighted that people with chronic conditions encounter significant challenges when self-management tools are not tailored to the specifics of their condition. Our studies have revealed a set of particular concerns that are relevant to the self-management of ME/CFS, from which we propose five high-level design recommendations.…”
Section: Discussion and Design Implicationssupporting
confidence: 81%
See 4 more Smart Citations
“…This work contributes a deeper understanding of ME/CFS patients' needs for self-management technologies. The studies also affirm the results of prior work [11,56], which has highlighted that people with chronic conditions encounter significant challenges when self-management tools are not tailored to the specifics of their condition. Our studies have revealed a set of particular concerns that are relevant to the self-management of ME/CFS, from which we propose five high-level design recommendations.…”
Section: Discussion and Design Implicationssupporting
confidence: 81%
“…Likewise, it is also important to note that the severity of ME/CFS for a given person can fluctuate on a daily basis. Many of our Study 2 participants described a lack of consistency in their symptoms from one day to the next, a phenomenon that has been observed in other chronic conditions [12,56].…”
Section: Discussion and Design Implicationsmentioning
confidence: 63%
See 3 more Smart Citations